Evaluation of Online Learning Implementation with a System Thinking Approach - Casnan, Casnan; Triwahyuni, Heti; Ropiah, Opah; Firmansyah, Irman (FKIP Universitas Lampung, 2022)
Evaluation of Student Online Learning with A System Thinking Approach. One of the successes of the learning process can be seen from the student's grades, but the overall evaluation process based on feedback from students can be done using systems thinking approach. Objective: The systems thinking approach in research aims to find out the obstacles to the online learning process and determine problem-solving strategies to improve the quality of online learning. Methods: The research method used is the descriptive qualitative method and Focus Group Discussion (FGD). Findings: Based on the results of the study, there are 20 variables of obstacles in the implementation of learning that are interrelated and influence the implementation of learning. Conclusion: The results of the study, it shows that the objective variables in learning are the learning process, student understanding of learning material, and value of learning outcomes, the supporting variables to answer the learning objectives are lecturer creativity and student motivation.Keywords: evaluation, learning, online, systems thinking.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202209